STUDY OF CHRONIC TOXICITY OF THE DRUG PHYTOFERON ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
The chronic toxicity of the tincture made from the collection"phytopheron" was studied in white rats in the experiment. The results showed that the drug is harmless to the body in amounts of 10 ml/kg and 25 ml/kg. The drug does not adversely affect peripheral blood-shaped elements, biochemical indicators and the histomorphological structure of internal organs in the amounts studied when administered for 30 days.